Total English intermediate - Clare, Antonia; Wilson, JJ; Pearson Education ([Harlow] : Pearson Education, 2006)
The grammar activities give a new ways to utilize the grammar points in each unit
Class CD1: Unit 1-Unit 5 (60 min.) -- Class CD2: Unit 6-Test B Units 6-10 (69 min.)
Title from container
Keywords: English language -- Problems, exercises, etc; English language -- Study and teaching -- Foreign speakers